0.3333
Chat with our AI personalities
To simplify the expression 3x divided by 9x, we first divide the coefficients: 3 ÷ 9 = 1/3. Then, we divide the variables: x ÷ x = 1. Therefore, the simplified expression is 1/3.
3X^2 + 9X/3X factor out 3X 3X(X + 3)/3X 3X/3X = 1, so... X + 3 is the simplest form here
3x. 15x - 9x = 6x 9x - 6x = 3x 6x - 3x = 3x 3x - 3x = 0
Apply the Distrubutive Property twice as you do when multiplying two-digit numbers Use the FOIL methed First Inner Outter Last. In the equation (3x + 4)(9x + 1) you get. (3x)*(9x) + (3x)*1 + (9x)*4 + 4*1 Now you multiply. 3x*9x = 27x^2 3x*1 + 9x*4 = 3x + 36x = 39x 1*4 = 4 So your entire answer is (3x)*(9x) + (3x)*1 + (9x)*4 + 4*1 = 27x^2 + 39x + 4
That factors to 3x(3x - 1)
It is a difference of squares. 9x^2-49=(3x+7)(3x-7)